Evaluation of two nematophagous fungi for the control of false root‑knot nematode Nacobbus aberrans in pepper crops - Bernardo, Valeria Fernanda (2023)
Nacobbus aberrans is an endophytic parasitic nematode that induces root galls, negatively affecting plant growth and devel- opment, and decreasing the production of economically important crops. Currently, low environmental impact alternatives are being developed for the control of nematodes, such as biological control agents, to reduce the use of soil disinfectants. Nematophagous fungi are microorganisms that can suppress nematode reproduction due to different mechanisms, such as parasitism of eggs, toxin production and stimulation of plant growth. The aim of this study was to investigate the effect of inoculation with nematophagous fungi on N. aberrans in greenhouse-grown pepper (Capsicum anuumm L.) plants and to analyze the response of the infected plants. Two fungal isolates, Purpureocillium lilacimum and Pleurotus ostreatus were tested. The plants were inoculated with these fungi at the time of transplantation in the presence and absence of N. aberrans. The reproduction factor of the nematode was 23.17; 5.90 and 36.4 for P. lilacinum, P. ostreatus and control, respectively. Both in plants parasitized and not parasitized by nematodes, the fungi increased the content of soluble proteins and photosynthetic pigments. Additionally, a favorable impact on growth parameters was also observed. This beneficial effect was also verified by a lower accumulation of proline and sugars, metabolites used by plants as osmoregulators in stress situations, and a low accumulation of malondialdehyde, a metabolite resulting from oxidative stress. These results show that both fungi are suit- able for use in the biocontrol of N. aberrans and as growth promoters in plants.